FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEND PAYOUT RATIO PADA PERUSAHAAN NON KEUANGAN - ISABELLA ISABELLA; APIT SUSANTI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this study was to examine if profitability,operating cash flow per share, corporate tax, current ratio, market to book value, debt to equityratio, firm size, and life cycle stage in affecting dividend payout ratio in non financial companies liested in Indonesia stock exchange. This research used 110 listed non financial companies in Indonesia Stock Exchange, selected using purposive sampling method in period 2012 to 2014. The data were analyzed using multiple regressions analysis method to determine the model of research. The result of the analysis indicated that profitability, operating cash flow per share, corporate tax, market to book value, debt to equity ratio,firm sizeandlife cycle stagehad influence on dividend payout ratio. But current ratio had no influence on dividend payout ratio.